Procesos de aprendizaje situado de los trabajadores de la construcción de la ciudad de Quito a través de la participación en prácticas sociales del oficio de la albañilería. - Cevallos Serrano, Daniela Alexandra (2017)
The purpose of this ethnography is to study the learning processes of the masonry trade through the analysis of the interactivities of a group of masons in the reconstruction project of the "Riofrío" house, a patrimonial building. This ethnography refutes the notion of learning, in this case of an office, as an individual process of acquisition of concepts that can only happen in isolation from other vital activities. Based on the theory of practice and situated learning, the central argument of this ethnography is that learning is a process that is embedded in human experience, and in the many forms of participation of people in the world, the world they dwell in and build, building themselves and others. The learning of the masonry trade happens in daily work, in the relationship with the veterans of the trade, as well as with peers, and in the practical and constant application of technical and social skills to incorporate them into their practice. The methodology used in this investigation was qualitative and contemplated: field work with anthropological participant observation, non-directive interviews, and conversations, photographic and video record. This work is organized along three moments/chapters: The conformation of "the oeuvre" in the “Riofrío” house as a landscape of tasks; the integration of the practice community of masons; and the social skills that are required and promulgated in that community of practice.